2009
DOI: 10.1136/ard.2008.090456
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and chronic widespread pain in a white middle-aged British population: evidence from a cross-sectional population survey

Abstract: Current vitamin D status was associated with CWP in women but not in men. Follow-up studies are needed to evaluate whether higher vitamin D intake might have beneficial effects on the risk of CWP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 44 publications
8
85
0
1
Order By: Relevance
“…There is some controversy among the experts as to which levels of 25-hydroxy vitamin D actually constitute deficiency (Holick 2007), but low levels of 25-hydroxy vitamin D have been linked with a higher incidence of chronic pain (Atherton 2009;Benson 2006;Lotfi 2007). Additionally, associations of such diverse types of pain as headache, abdominal pain, knee pain, and back pain with season of the year and latitude may be taken as evidence to suggest that 25-hydroxy vitamin D levels are important in this context (Mitsikostas 1996;Saps 2008;Zeng 2004).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…There is some controversy among the experts as to which levels of 25-hydroxy vitamin D actually constitute deficiency (Holick 2007), but low levels of 25-hydroxy vitamin D have been linked with a higher incidence of chronic pain (Atherton 2009;Benson 2006;Lotfi 2007). Additionally, associations of such diverse types of pain as headache, abdominal pain, knee pain, and back pain with season of the year and latitude may be taken as evidence to suggest that 25-hydroxy vitamin D levels are important in this context (Mitsikostas 1996;Saps 2008;Zeng 2004).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…Both cases presented with similar complaints of depression, 10,40-42 fatigue, [43][44][45] and muscle aches, 44,[46][47][48] all of which have been previously associated with vitamin D deficiency. However, there are no current studies correlating a loss of smell with vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 98%
“…In studies, however, it is reported that a low level of vitamin D is a common symptom in those with non-specific and chronic musculoskeletal pain. Especially, the association between low level of vitamin D and pain in osteomalacia is well established (20)(21)(22)(23)(24). Moreover, there are also studies reporting that a definite improvement is seen at the level of pain after vitamin D supplementation in patients with non-specific and chronic musculoskeletal system pain and vitamin D deficiency (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%